2010
DOI: 10.1016/j.atmosenv.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of residential wood combustion to PM10 levels in Portugal

Abstract: a b s t r a c tWood is commonly used in residential combustion for heating purposes; however, it can be a major source of air pollutants, namely fine particles, volatile organic compounds and carbon monoxide. Since 2004, the PM10 daily limit value has been surpassed in Portugal, and the European Commission has stated that plans and programs must be designed in order to reduce these levels. In Portugal, 18% of PM10 emissions are due to residential wood combustion, which may deeply impact the PM10 levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…In Europe, emissions from biomass combustion are one of the major sources of atmospheric aerosol mass during winter Gelencsér et al, 2007). Modelling results showed that in Portugal 18% of PM 10 could be related to this emission source, which may deeply impact the levels in the atmosphere (Borrego et al, 2010). Source apportionment of PM 2.5 aerosol applied to ambient measurements in a coastal/rural area in Portugal showed that 52e69% of the organic carbon is assigned to residential wood burning for heating .…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, emissions from biomass combustion are one of the major sources of atmospheric aerosol mass during winter Gelencsér et al, 2007). Modelling results showed that in Portugal 18% of PM 10 could be related to this emission source, which may deeply impact the levels in the atmosphere (Borrego et al, 2010). Source apportionment of PM 2.5 aerosol applied to ambient measurements in a coastal/rural area in Portugal showed that 52e69% of the organic carbon is assigned to residential wood burning for heating .…”
Section: Introductionmentioning
confidence: 99%
“…The anthropogenic sources of PM10 are usually located in urban and industrial areas. Over the urban areas, the emission of PM10 is closely related to residential combustion (Borrego et al, 2010a), construction and road traffic. Traffic emissions are due not only to the direct exhaust of the vehicles, but also to brakes wear, road abrasion, tyre wear and road dust re-suspension.…”
Section: Measures To Reduce the Pm10 Emissions Over The Northern Regimentioning
confidence: 99%
“…Borrego et al (2010a) estimated an 18% contribution of this residential combustion to the total PM10 emissions in Portugal, and that 98% of these originate from the burning of biomass. Consequently, the regulation of this sector, particularly the certification of equipment with lower PM10 emission rates, will contribute to air quality improvement (both outdoors and indoors).…”
Section: Residential Combustion Sectormentioning
confidence: 99%
“…Vulnerable to these harmful substances are women who spend most of their time in the cooking area, and young children who often stay close to their mothers around the cooking area. Previous studies have indicated that the levels of indoor air pollution from biomass fuels can be astonishingly high, often higher than ambient air quality standards in some developing countries [3,4]; and can impact the ambient air from indoor residential wood burning [5,6]. Empirical evidence suggests that burning biomass fuels increases the risk of acute respiratory infections, chronic obstructive pulmonary diseases, asthma and tuberculosis, etc.…”
Section: Introductionmentioning
confidence: 99%